Government ideology, democracy and the sacrifice ratio: Evidence from Latin American and Caribbean Disinflations - Tony Caporale (The Open Economics Journal, 2011)
This study uses a sample of 34 disinflations undertaken by thirteen Latin American and Caribbean (LAC) nations to test if political institutions impact the cost of policy induced disinflations. We find, after controlling for several of the most important covariates in the literature, that disinflations are less costly for right vs left governments and that sacrifice ratios are lower for more democratic vs authoritarian governmental regimes. This is robust to different measures of government ideology as well as to alternative ways of computing the sacrifice ratio and lends support for political economy literature which argues that political institutions have significant macroeconomic effects.
Keywords: 330; sacrifice ratio; disinflation; political regimes